Pendampingan Pengelolaan Risiko Usaha Mikro Kecil Menengah untuk Keberlanjutan Bisnis - Dewi Cahyani Pangestuti; Heni Nastiti; Renny Husniati; Sumilir Sumilir (TAAWUN, 2024)
Currently, many Micro, Small, and Medium Enterprises (MSMEs), including Kopi Kotak located in Depok, are not yet aware of the importance of risk management and do not have structured procedures to identify risks. The purpose of this community service is to provide direct assistance and guidance to Kopi Kotak MSMEs regarding risk management so that they can improve their business capabilities and sustainability. This service involves conducting observations and interviews with employees of Kopi Kotak MSME to formulate a risk register based on the research results. The research identified six main risks faced by Kopi Kotak MSMEs, including raw material shortages, equipment, raw material quality, compliance, weather, and changes in raw material prices and rent. With guidance, Kopi Kotak MSMEs received assistance in creating a comprehensive risk identification plan. This included identifying the root causes of risks, providing risk assessments, and formulating risk mitigation recommendations. This process aims to increase the awareness and readiness of Kopi Kotak MSMEs in managing day-to-day operational risks.